The correct answer will be the first one, (-1,0). Since it gives you the points the first point will be x and the second point will be y. All you have to do is plug those points into the equation and see if it is the correct answer if not go onto the next points until you reach the correct one.
Answer:
Step-by-step explanation:
1.
![3 :7 \\Acute \: angle = 90\°\\7+3 = 10\\\frac{7}{10} \times 90\\\\= \frac{630}{10}\\ = 63 \°\\](https://tex.z-dn.net/?f=3%20%3A7%20%5C%5CAcute%20%5C%3A%20angle%20%3D%2090%5C%C2%B0%5C%5C7%2B3%20%3D%2010%5C%5C%5Cfrac%7B7%7D%7B10%7D%20%5Ctimes%2090%5C%5C%5C%5C%3D%20%5Cfrac%7B630%7D%7B10%7D%5C%5C%20%3D%2063%20%5C%C2%B0%5C%5C)
2.
![Let \:the\: other\:acute \:angle\: be \:x\\According\:to \:the \:question ; \\ \:\\(2x-30)+x =90\\2x - 30 +x =90\\2x +x = 90+30\\3x = 120\\\frac{3x}{3} =\frac{120}{3} \\x = 40 \\\\(2x -30)\\2(40) -30\\80 - 30 = 50\\\\\\Angle \:1 = 50\°\\Angle \: 2 = 40\°\\](https://tex.z-dn.net/?f=Let%20%5C%3Athe%5C%3A%20other%5C%3Aacute%20%5C%3Aangle%5C%3A%20be%20%5C%3Ax%5C%5CAccording%5C%3Ato%20%5C%3Athe%20%5C%3Aquestion%20%3B%20%5C%5C%20%5C%3A%5C%5C%282x-30%29%2Bx%20%3D90%5C%5C2x%20-%2030%20%2Bx%20%3D90%5C%5C2x%20%2Bx%20%3D%2090%2B30%5C%5C3x%20%3D%20120%5C%5C%5Cfrac%7B3x%7D%7B3%7D%20%3D%5Cfrac%7B120%7D%7B3%7D%20%5C%5Cx%20%3D%2040%20%5C%5C%5C%5C%282x%20-30%29%5C%5C2%2840%29%20-30%5C%5C80%20-%2030%20%3D%2050%5C%5C%5C%5C%5C%5CAngle%20%5C%3A1%20%3D%2050%5C%C2%B0%5C%5CAngle%20%5C%3A%202%20%3D%2040%5C%C2%B0%5C%5C)
1)X×Y that is the equation
Answer:
x = 14
General Formulas and Concepts:
<u>Pre-Algebra</u>
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
3x - 5 = 37
<u>Step 2: Solve for </u><em><u>x</u></em>
- [Addition Property of Equality] Add 5 on both sides: 3x = 42
- [Division Property of Equality] Divide 3 on both sides: x = 14
Answer:
m+16
Step-by-step explanation:
"16 more than m" is another way of saying "16 added to m". This is the same as 6 plus m or m plus 6. Therefore, the expression form of "16 more than m" is m+16 or 16+m.